Effects of Denaturation on the Structure and Properties of Soy Protein Composites - Eyler, Allen; Liu, Tian; Scudiero, Louis; Wo, Pui Ching; Zhong, Wei-Hong (Journal of Composites and Biodegradable Polymers, 2015)
Soy protein (SP), a widely abundant biomaterial with a high concentration of polar and reactive functional groups and a complex three dimensional structure, has frequently been used in polymer blends and composites. However, few studies have focused on the critical role of denaturation in the application of SP to composites. The denaturation conditions profoundly affect the protein structure at scales approaching the molecular level and therefore can be expected to significantly influence the morphology and properties of SP-containing composites. In this study, the influences of three SP denaturation methods on the structures and properties of the poly(ethylene oxide) (PEO) composite films were compared. Of these methods, urea treatment followed by dialysis process results in the most effective denaturation, with nanoscale SP particle size and high PEO/SP interfacial area, stable dielectric properties, and super-elasticity resulting from improved PEO/SP interactions. This work guides the customization of biocomposite properties via the control of denaturation conditions.